1991
DOI: 10.1037/0735-7044.105.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Temporal resolution of gaps in noise by the rat is lost with functional decortication.

Abstract: In Experiment 1 (n = 8), the rat's ability to detect brief gaps in white noise was measured by gap-produced inhibition of an acoustic startle reflex, elicited 100 ms after the gap. After bilateral application of KCl to the cortex, gaps as long as 15 ms provided no reflex inhibition; in contrast, the inhibitory threshold was between 2 and 4 ms in the saline control condition. In Experiment 2 (n = 13), noise pulses of 40, 50, or 70 dB were presented 20-500 ms before the startle stimulus, and in Experiment 3 (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
121
1
4

Year Published

1993
1993
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(149 citation statements)
references
References 31 publications
18
121
1
4
Order By: Relevance
“…Consistent with previous research (lson, 1982;Ison et al, 1991), a gap in otherwise continuous noise reliably reduced the amplitude of the rat's acoustic startle reflex. Also consistent with previous research (e.g., Marsh et al, 1975;Schwartz, Hoffman, Stitt, & Marsh, 1976), an inverse relationship was found between reflex amplitude reduction and stimulus saliency-the larger the gap, the greater the degree of reflex reduction.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Consistent with previous research (lson, 1982;Ison et al, 1991), a gap in otherwise continuous noise reliably reduced the amplitude of the rat's acoustic startle reflex. Also consistent with previous research (e.g., Marsh et al, 1975;Schwartz, Hoffman, Stitt, & Marsh, 1976), an inverse relationship was found between reflex amplitude reduction and stimulus saliency-the larger the gap, the greater the degree of reflex reduction.…”
Section: Discussionsupporting
confidence: 90%
“…More recently, Ison, O'Connor, Bowen, and Bocirnea (1991) essentially replicated these findings in rats; gaps presented at short SOAs continued to increase in their ability to reduce startle amplitude as their duration increased from 2 to 30 msec. Gaps presented at long SOAs produced a maximum degree of reflex reduction at durations of 4 msec, beyond which increases in duration did not cause further reductions of startle amplitude.…”
mentioning
confidence: 56%
See 3 more Smart Citations